Role of G protein‐coupled receptor kinase 2 in oxidative and nitrosative stress‐related neurohistopathological changes in a mouse model of sepsis‐associated encephalopathy. Issue 6 (16th May 2018) - Kawakami, Masaaki; Hattori, Mizuki; Ohashi, Wakana; Fujimori, Toshio; Hattori, Kohshi; Takebe, Mariko; Tomita, Kengo; Yokoo, Hiroki; Matsuda, Naoyuki; Yamazaki, Mitsuaki; Hattori, Yuichi
Abstract : Sepsis‐associated encephalopathy (SAE) represents diffuse cerebral dysfunction and can give rise to poor outcome in sepsis, but the mechanisms underlying its pathogenesis remain largely to be elucidated and any effective therapy against SAE is lacking. Here, we show the novel role for G protein‐coupled receptor 2 (GRK2) in regulating microglial oxidative and nitrosative stress, which can lead to sepsis‐related neurohistological damage. We propose that GRK2 may serve as an intriguing therapeutic target for the prevention or treatment of SAE. Abstract: Sepsis‐associated encephalopathy (SAE), characterized as diffuse brain dysfunction and neurological manifestations secondary to sepsis, is a common complication in critically ill patients and can give rise to poor outcome, but understanding the molecular basis of this disorder remains a major challenge. Given the emerging role of G protein‐coupled receptor 2 (GRK2), first identified as a G protein‐coupled receptor (GPCR) regulator, in the regulation of non‐G protein‐coupled receptor‐related molecules contributing to diverse cellular functions and pathology, including inflammation, we tested the hypothesis that GRK2 may be linked to the neuropathogenesis of SAE. When mouse MG6 microglial cells were challenged with lipopolysaccharide (LPS), GRK2 cytosolic expression was highly up‐regulated. The ablation of GRK2 by small interfering RNAs (siRNAs) prevented an increase in intracellular reactive oxygen species generation in LPS‐stimulated MG6 cells. Furthermore, the LPS‐induced up‐regulation of inducible nitric‐oxide synthase expression and increase in nitric oxide production were negated by GRK2 inhibitor or siRNAs. However, GRK2 inhibition was without effect on overproduction of tumor necrosis factor‐α, interleukin (IL)‐6, and IL‐1β in LPS‐stimulated MG cells. In mice with cecal ligation and puncture‐induced sepsis, treatment with GRK2 inhibitor reduced high levels of oxidative and nitrosative stress in the mice brains, where GRK2 expression was up‐regulated, alleviated neurohistological damage observed in cerebral cortex sections, and conferred a significant survival advantage to CLP mice. Altogether, these results uncover the novel role for GRK2 in regulating cellular oxidative and nitrosative stress during inflammation and suggest that GRK2 may have a potential as an intriguing therapeutic target to prevent or treat SAE.